Support the implementation of 2025 International Forum of Low-Emission Agrifood Systems such as organizing a low carbon food system workshop at WAFI in China and conducting consultation to prioritize mitigation option for China - CGIAR Science Program on Climate Action (CGIAR System Organization, 2025)
Agriculture is one of the sectors most directly and vulnerable to the impacts of global climate change. In recent years, the continuous rise in global temperatures and the frequent occurrence of extreme weather events have been profoundly changing the environment and conditions for agricultural production, posing severe challenges to global food security, farmers' livelihoods, and the sustainable development of agriculture. Technologies from climate-smart agriculture and biological breeding to digital technology and artificial intelligence, technological innovation have provided new solutions to global challenges. However, research and development by individual agricultural scientists and research institutions is no longer sufficient to fully unleash the potential of science and technology to address these complex issues. This calls on the global scientific community to break down geographical and disciplinary barriers, and pool the scattered innovation forces into a holistic strategy for synergistic effects through deepening international cooperation and knowledge sharing.